Cooperation between Corporations and NGOs for Sustainability in Supply Chain: A Structured Literature Review - Oumcharoen, Parichaya (2017)
This structured literature review aims to identify the roles, trigger and results from the cooperation between corporations and NGOs in order to create sustainability in supply chain. The research reveals that there is the overlap in both roles and triggers in both from perspective of NGOs and corporations. The ultimate role that performed by both parties is sharing knowledge as it a consequence of the lack of knowledge which drive both parties to seek for partners to assist to achieve the certain goals. Besides that, the goals from both point of view are usually related but the corporations definitely expected to gain profit while NGOs anticipated to see the improvement within the society. Furthermore, the author also described the limitation as well as future research implications.